The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1289/ehp.01109893
|View full text |Cite
|
Sign up to set email alerts
|

Allium vegetables and organosulfur compounds: do they help prevent cancer?

Abstract: The Allium genus includes approximately 500 species, the most widely used of which are onions (Allium cepa), garlic (Allium sativum), leeks (Allium porrum), chives (Allium schoenoprasum), and shallots (Allium ascalonicum). Garlic is widely cultivated and consumed worldwide, and its beneficial effects have been known for thousands of years. It has been considered to increase longevity and to confer stamina and physical strength, and it has been used empirically as a vermifuge, antiseptic, antimicrobic, antipyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(77 citation statements)
references
References 112 publications
(156 reference statements)
2
63
0
2
Order By: Relevance
“…has been used as a stimulant (Hamel, 1975) (Supplementary Table 3). We note that similar pro-health effects have been reported for different Allium species, likely because these species have a similar chemical content characterized by high levels of organosulfur compounds (Bianchini and Vainio, 2001; Rahman, 2003; Rose et al, 2005). Amelanchier alnifolia has febrifuge and tonic properties and is used as an adjuvant for medicinal preparations (Leighton, 1985; Turner, 1980) (Supplementary Table 3).…”
Section: Resultssupporting
confidence: 75%
“…has been used as a stimulant (Hamel, 1975) (Supplementary Table 3). We note that similar pro-health effects have been reported for different Allium species, likely because these species have a similar chemical content characterized by high levels of organosulfur compounds (Bianchini and Vainio, 2001; Rahman, 2003; Rose et al, 2005). Amelanchier alnifolia has febrifuge and tonic properties and is used as an adjuvant for medicinal preparations (Leighton, 1985; Turner, 1980) (Supplementary Table 3).…”
Section: Resultssupporting
confidence: 75%
“…Among the hundreds of species in the Allium genus, garlic ( Allium sativum ) is particularly well-known for its beneficial effects and has been widely consumed, cultivated, and researched worldwide for centuries. To date, the evidence for inverse association between garlic intake and gastric cancer risk was based primarily on the results from case-control studies 5, 710 . Compared to cohort studies, case-control studies are more prone to biases such as recall bias, selection bias, and reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we have limited knowledge on the stability of the organosulfur compounds during cooking 7 . An experimental study suggested that cooked garlic no longer has beneficial effects, at least in carcinogenesis 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gut bacteria were also reported to engender significant amount of H 2 S [5]. Furthermore, human diet that is rich in organosulfur compounds such as garlic, onions, leeks and chives have been reported to contribute to H 2 S pool and to exert significant influence on the metabolic state and hypertension [6]. Nonetheless, regulated H 2 S production at defined tissue milieu and sub-cellular spaces occurs through specific enzymes.…”
mentioning
confidence: 99%